Primer reporte de specularius impressithorax (pic) (coleoptera: bruchidae) alimentándose de semillas de erythrina americana miller en los estados de Veracruz y Morelos, México - Ruí Montiel, César; Marina-Hernández, María de Jesús; Romero Nápoles, Jesús; Ríos Reyes, Angélica Verónica (Instituto de Ecología, A.C., 2012)
In this note, we report the first record of Specularius impressithorax (Pic) (Coleoptera: Bruchidae) in seeds of Erythrina americana. The flowers of this plant are used as food or as a commercial commodity. The presence of this insect could therefore cause economic damage to the region.